Prevalence and antimicrobial resistance of Salmonella isolated from an integrated broiler chicken supply chain in Qingdao, China. (April 2016) - Cui, Mingquan; Xie, Maoying; Qu, Zhina; Zhao, Sijun; Wang, Junwei; Wang, Yang; He, Tao; Wang, Hongyu; Zuo, Zhicai; Wu, Congming
Abstract: The present study analyzed the prevalence and antimicrobial resistance of Salmonella along an integrated broiler chicken supply chain. A total of 172 Salmonella isolates were recovered from 1148 samples collected from four sample sources (breeder farms, broiler farms, abattoir, and retail markets), representing nine production stages. These Salmonella isolates were examined for antimicrobial susceptibility to 12 different antimicrobial agents using a disk diffusion assay. Among them, 168 were identified as six different serotypes of Salmonella enterica. The predominant serotype was S. Enteritidis (n = 116), followed by S. Infantis (n = 18), S. Gueuletapee (n = 16), S. Derby (n = 12), S. Meleagridis (n = 4), and S. London (n = 2). The remaining four isolates were serogroup-untypeable. A majority of the 172 isolates (96.51%) was resistant to one or more antibiotics and 61.05% of the Salmonella isolates showed a multidrug resistance phenotype. Statistical analysis indicated the one risk product stage for Salmonella contamination occurred in the sample source at the abattoir, specifically the stage of Carcasses after chilling. The majority of S. Enteritidis isolates shared the same pulsed-field gel electrophoresis (PFGE) cluster, suggesting that the S. Enteritidis strain might spread along the broiler chicken supply chain. The prevalence and antimicrobial resistance of Salmonella in different production stages suggest the importance of controlling Salmonella in the broiler chicken supply chain for public health, underlying the need for improved measures of reducing carcass contamination in abattoirs and the appropriate use of antimicrobials in broiler flocks.